2011
DOI: 10.1074/jbc.m110.170241
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Surfactant Phosphatidylglycerol Inhibits Mycoplasma pneumoniae-stimulated Eicosanoid Production from Human and Mouse Macrophages

Abstract: Mycoplasma pneumoniae is a human pathogen causing respiratory infections that are also associated with serious exacerbations of chronic lung diseases. Membranes and lipoproteins from M. pneumoniae induced a 4-fold increase in arachidonic acid (AA) release from RAW264.7 and a 2-fold increase in AA release from primary human alveolar macrophages. The bacterial lipoprotein mimic and TLR2/1 agonist Pam3Cys and the TLR2/6 agonist MALP-2 produced effects similar to those elicited by M. pneumoniae in macrophages by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 54 publications
2
84
2
Order By: Relevance
“…POPG is an effective antagonist of Toll-like receptor 4 (TLR4) activation and acts by disrupting interactions of lipopolysaccharide (LPS) with cluster of differentiation 14 (CD14) and lymphocyte antigen 96 (MD2) (21)(22)(23)(24). The lipid also antagonizes Toll-like receptor 2 (TLR2) activation by inhibiting signaling from the cell surface ( 25 ). The antiviral actions of POPG include its activity against RSV and infl uenza A virus ( 18,19 ).…”
Section: In Vivo Rsv Infection and Its Prevention By Popgmentioning
confidence: 99%
See 2 more Smart Citations
“…POPG is an effective antagonist of Toll-like receptor 4 (TLR4) activation and acts by disrupting interactions of lipopolysaccharide (LPS) with cluster of differentiation 14 (CD14) and lymphocyte antigen 96 (MD2) (21)(22)(23)(24). The lipid also antagonizes Toll-like receptor 2 (TLR2) activation by inhibiting signaling from the cell surface ( 25 ). The antiviral actions of POPG include its activity against RSV and infl uenza A virus ( 18,19 ).…”
Section: In Vivo Rsv Infection and Its Prevention By Popgmentioning
confidence: 99%
“…We previously reported that simultaneous addition of POPG and RSV to human bronchial epithelial cells (either BEAS2B cells or primary cultures of human bronchial Multiple molecular species of PG bind to RSV with high affi nity Previous studies have reported that the anionic phospholipid antagonism of LPS activation of macrophages through CD14/MD2/TLR4 and the anionic phospholipid antagonism of TLR2 activation are specifi c to the molecular class and species of phospholipid used as an antagonist (21)(22)(23)(24)(25). Pulmonary surfactant contains several molecular species of PG in addition to POPG ( 16,19 ).…”
Section: Popg Inhibits Il-8 Production After Rsv Infection Is Establimentioning
confidence: 99%
See 1 more Smart Citation
“…ToF-SIMS studies have demonstrated that phosphatidylglycerols concentrate along the edges of the tubular proteolipids that form the tubular myelin of pulmonary surfactant and are dispersed throughout the interstitial space between the tubular networks [24]. Of further significance are the observations that phosphatidylglycerols regulate innate immunity against lung viral infections and the associated inflammatory processes [23][24][25][26][27][28][29][30][31]. Recent studies have also demonstrated in murine models that phosphatidylglycerol administration is effective both for postinfection treatment and for prophylaxis against respiratory syncytial viral infections [32], a predominant respiratory pathogen in young children.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence now demonstrates that ex tracellular PG plays a critical role in regulating the innate immune system within the lung (2,(10)(11)(12)(13)(14)(15)(16) by competi tively antagonizing liganddependent activation of tolllike receptor (TLR)1, TLR2, TLR4, and TLR6 (13,14). This antagonism prevents the production of protein inflamma tory mediators, such as TNF and interleukins 6 and 8, and lipid inflammatory mediators, such as prostaglandin D2, thromboxane A2, and leukotriene C4 (11,13,14).…”
mentioning
confidence: 99%